Increasing days on feed for heavy short-fed yearling stocker cattle improves carcass characteristics - A. Stickel; Terry A. Houser; K. C. Olson; B. Gerlach; B. Goehring; A. Pacheco; M. Macek; G. Parsons; K. Miller; L.K. Thompson; S. James (Kansas Agricultural Experiment Station Research Reports, 2011)
With increasing feed costs, producers may be able to utilize forage resources to help cattle gain weight before entering a high-concentrate finishing phase. In theory, heavy stocker cattle need less time on feed before slaughter compared to lighter weight cattle; however, research determining the impact of a short feeding system on product quality is limited. Therefore, the purpose of this research was to investigate the impact of a shortened, high-concentrate feeding period on carcass characteristics and meat quality traits of heavy yearling stocker cattle.
Keywords: Kansas Agricultural Experiment Station contribution; no. 11-171-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1047; Cattlemen& #x27; s Day; 2011; Beef; Stocker cattle; Carcass characteristics; Performance; Dried distillers grains